PENDUGAAN UMUR SIMPAN BUBUK JAHE MERAH (Zingiber officinale var. rubrum) - Indah Yuliasih, Sugiarto dan Tedy (Jurnal Teknologi Industri Pertanian, 2006)
ABSTRACTRed ginger is one kind of ginger, which is usually used for modern and traditional herb medicine. Fresh red ginger is easily damage; therefore preservation technology is needed. Red ginger preserved by drying or being fermented as pickle. Red ginger powder is another preservation method that has advantages in better transportation and storage purposes. Red ginger powder is the main product used for base or supplement material in drug industry. Furthermore it is not only consumed in powder form but also being extracted to yield an oleoresin and essential oil. During the storage period, the quality of red ginger powder can decrease; therefore shelf life dating of red ginger powder is needed.Red ginger is dried in 1m3 cabinet dryer at 55 OC and 30 % relative humidity, under that circumstances, the red ginger‘s moisture content follows the equation Y = 123.47e-0.0203x; as the result red ginger must be dried for approximately 135 minutes to get 7.41 % of moisture content. The constant period ended at 30th minute of drying process. This point also known as critical moisture content of red ginger’s drying process, at this point red ginger has 37.00 % of moisture content.Red ginger powder without filler has the longest shelf life. At 25 OC it has 629 days of shelf life. Shelf life at 30 OC is 544 days, 343 days for shelf life at 40 OC, 1500 days for shelf life at 10 OC and 593 days of shelf life at 28 OC. Red ginger powder’s shelf life will generally decrease with filler’s addition.Keyword : ……………..